United tweets of America - Talbott, Hudson (New York : G.P. Putnam's Sons, 2008)
A collection of detailed illustrations of state birds from all fifty United States.
Wilson's Children, October 2010.
School Library Journal starred, May 2008.
Book Links (A.L.A.), December 2008.
Pub Weekly, May 2008.
Booklist, April 2008.
Horn Book, October 2008.
Keywords: U.S. states -- Miscellanea -- Juvenile literature; State birds -- United States -- Juvenile literature; U.S. states -- Miscellanea; State birds -- United States; U.S. states -- Miscellanea; State birds; State birds; United States -- Miscellanea -- Juvenile literature; United States -- Miscellanea; United States -- Miscellanea; United States -- Miscellanea